2022
DOI: 10.3390/tropicalmed8010018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Regulatory T Cells in Patients Infected by Leishmania Infantum

Abstract: High IL-10 levels are pivotal to parasite survival in visceral leishmaniasis (VL). Antigenic stimuli induce IL-10 expression and release of adenosine by CD39/CD73. Due their intrinsic ability to express IL-10 and produce adenosine from extracellular ATP, we evaluated the IL-10, CD39, and CD73 expression by Regulatory T cells (Treg) correlated with VL pathology. Using flow cytometry, Treg cells was analyzed in peripheral blood samples from VL patients (in the presence and absence of Leishmania infantum soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In a model of VL infection, it has been suggested that transition of the inflammatory milieu to a regulatory milieu, shown by the increased B-cell activity and IL-10 levels, is associated with the establishment of chronic infection and accumulation of Leishmania parasites in the skin ( 104 ). In human leishmaniasis, IL-10 plays a central role in the course of the immune response in VL, contributing to the chronicity of the disease through suppression of host immunity and effector T-cell functions ( 59 , 106 , 107 ). Indeed, it was shown that elevated levels of plasma IL-10 and IL-10 expression by keratinocytes indicate the likelihood of subsequent PKDL development in VL patients following treatment ( 108 ).…”
Section: Persistent Parasites and Concomitant Immunitymentioning
confidence: 99%
“…In a model of VL infection, it has been suggested that transition of the inflammatory milieu to a regulatory milieu, shown by the increased B-cell activity and IL-10 levels, is associated with the establishment of chronic infection and accumulation of Leishmania parasites in the skin ( 104 ). In human leishmaniasis, IL-10 plays a central role in the course of the immune response in VL, contributing to the chronicity of the disease through suppression of host immunity and effector T-cell functions ( 59 , 106 , 107 ). Indeed, it was shown that elevated levels of plasma IL-10 and IL-10 expression by keratinocytes indicate the likelihood of subsequent PKDL development in VL patients following treatment ( 108 ).…”
Section: Persistent Parasites and Concomitant Immunitymentioning
confidence: 99%